Axial super resolution topography of focal adhesion by confocal microscopy. Issue 10 (29th July 2013) - Chiu, Chi‐Li; Gratton, Enrico
ABSTRACT The protein organization within focal adhesions has been studied by state‐of‐the‐art super resolution methods because of its thin structure, well below diffraction limit. However, to achieve high axial resolution, most of the current approaches rely on either sophisticated optics or diligent sample preparation, limiting their application. In this report we present a phasor‐based method that can be applied to fluorescent samples to determine the precise axial position of proteins using a conventional confocal microscope. We demonstrate that with about 4, 000 photon counts collected along a z‐scan, axial localization precision close to 10 nm is achievable. We show that, with within 10 nm, the axial location of paxillin, FAK, and talin is similar at focal adhesion sites, while F‐actin shows a sharp increase in height towards the cell center. We further demonstrated the live imaging capability of this method. With the advantage of simple data acquisition and no special instrument requirement, this approach could have wide dissemination and application potentials. Microsc. Res. Tech., 76:1070–1078, 2013. © 2013 Wiley Periodicals, Inc.